2006
DOI: 10.1111/j.1365-2710.2006.00729.x
|View full text |Cite
|
Sign up to set email alerts
|

Cefepime vs. Ampicillin/Sulbactam and Aztreonam as antibiotic prophylaxis in neurosurgical patients with external ventricular drain: result of a prospective randomized controlled clinical trial

Abstract: Single board spectrum antibiotic prophylaxis with Cefepime was an effective alternative regimen for neurosurgical patients with an EVD in situ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 14 publications
(24 reference statements)
1
18
0
Order By: Relevance
“…AMS have been confirmed by numerous studies (mainly comparative) carried out in more recent years [30,[106][107][108][109][110][111][112][113][114][115][116][117] (Table 8). Thus, there is good evidence for AMS (typically given in one or more doses of 1-2 g ampicillin/0.5-1 g sulbactam i.v.…”
Section: Antibiotic Prophylaxissupporting
confidence: 51%
“…AMS have been confirmed by numerous studies (mainly comparative) carried out in more recent years [30,[106][107][108][109][110][111][112][113][114][115][116][117] (Table 8). Thus, there is good evidence for AMS (typically given in one or more doses of 1-2 g ampicillin/0.5-1 g sulbactam i.v.…”
Section: Antibiotic Prophylaxissupporting
confidence: 51%
“…The periprocedural administration of antibiotics with the aim of preventing ventriculostomy-related infections is not a completely resolved issue [12][13][14][15][16][17][18]. First-and second-generations cephalosporins have been used as prophylactic antibiotics for this procedure [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Data from most published clinical trials indicate that SSIs are primarily associated with gram-positive bacteria, S. aureus, and coagulase-negative staphylococci. 6,8,[537][538][539][540][541][542][543][544][545][547][548][549][550][551][552][553][554] Several cohort studies revealed high rates (up to 75-80% of isolates) of MRSA 540-543,548-552 and coagulasenegative staphylococci among patients undergoing a variety of neurosurgical procedures. 539,540,543,549 Other skin organisms such as P. acnes may be seen after CSF shunt placement, craniotomy, and other procedures.…”
Section: Neurosurgery Proceduresmentioning
confidence: 99%